The sinecism of Megalopolis and the origin of the Arcadian confederation - María Cruz CÁRDETE DEL OLMO (Studia Historica: Historia Antigua, 2013)
Megalopolis had a great area of expansion (1.500 km2) which embraces the centre and south of Arcadia. The sinecism of Megalopolis was possible thank the territories of Pharrasia, Menalia and Eutresia tribes. This sinecism involved a great demographic and cultural change which created many political problems. Megalopolis fought again them through ideological manipulation based on religion and beliefs. Moreover, the Megalopolis foundation was the origin of the Arcadian Confederation which tried, for some years, to transform this region into a reference of Greek politics.